2021
DOI: 10.36941/jesr-2021-0104
|View full text |Cite
|
Sign up to set email alerts
|

Instrument Development for Socio-Educational Support and Socio-Educational Participation towards Educational Well-Being

Abstract: The current study aims to develop and validate a questionnaire instrument to measure the socio-environmental support, socio-educational participation and educational well-being indicators using Exploratory Factor Analysis (EFA) and Reliability Analysis among secondary school children in Sri Lanka. The indicators used in the analyses were based on sociological theories, and several past empirical studies identified to have three main constructs. The socio-environmental support construct which is based on Bronfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In the context of student learning, socio-environmental support from home, school, community, and virtual platforms is crucial for enhancing student engagement, leading to educational achievement and well-being. This underscores the interconnectedness of support systems in fostering positive learning outcomes [12].…”
Section: Socio-environmental Supportmentioning
confidence: 98%
See 1 more Smart Citation
“…In the context of student learning, socio-environmental support from home, school, community, and virtual platforms is crucial for enhancing student engagement, leading to educational achievement and well-being. This underscores the interconnectedness of support systems in fostering positive learning outcomes [12].…”
Section: Socio-environmental Supportmentioning
confidence: 98%
“…Socio-environmental support also influences students' motivation, contributing to their wellbeing. Careemdeen et al [12], showed that environmental support from parents, teachers, peers, and the community correlated with higher academic well-being. Bofah and Ntow [13],demonstrated that perceived parent and teacher support influenced students' selfconfidence and self-concept, with teacher support being the most influential predictor.…”
Section: Socio-environmental Supportmentioning
confidence: 99%